A study of print and computer-based reading to measure and compare rates of comprehension and retention. Issue 7 (8th July 2014) - Young, Jackie
Abstract : Purpose: – This paper aims to observe, measure and record comparative cognitive processes in print and online to explain the differences, if any, in the readers' information-gathering processes and their subsequent comprehension and retention of information. It also examined the strategies that readers adopt that differ from print when reading online. Standardized reading comprehension scores were also collected. The results indicated that the participants demonstrated functional equivalency in both media, but they had a preference for print. The linear individualistic mentality learned through print gave the study group participants the skills to successfully navigate through the dense web of information that constitutes the Internet. Story presentation and hierarchy, key elements of the print design process, are less evident or absent online. As a consequence, as previous research has demonstrated, online readers are more poorly informed than print readers – but not in this case. The research from this study demonstrates that when the authors of the print media are those who also control the integrity of online content, print and Web readers are equally well-informed. Design/methodology/approach: – Coded texts from The Guardian Newspaper, The Economist and The New Yorker were used in a media lab to measure the study group's ability to read and retrieve information from the publications' print and Web editions. They were scored on how well they retrieved the core information in the articles from both media. Focus-group sessions probed for information about reading in print and online at the end of the reading sessions. This gave valuable insight into the coping strategies that the participants used when engaging with online texts. There were two sessions, each of three hours, and the participants were university students. Findings: – The study results show that the group participants were functionally equivalent in both print and online reading. However, they had a profound distrust for online content in general, which they found to be inaccurate and unstable. Web sites, they conclude, never achieve "fixity". When reading online, the study group scrolls through the text to retrieve facts and then goes to a print source to verify the accuracy of the content. They do not engage with the content online as they do with print. While acknowledging that the publications in the study were reputable and of a high quality, the group still found scrolling through the Web sites tedious. The printed page was to the study group, a cultural object. Research limitations/implications: – This was a small study with 11 participants in a controlled environment on two evenings, each lasting three hours. While the readings were intense, the researchers saw no evidence of fatigue. The group were very vocal during the focus-group sessions and gave valuable insights into the reading process. The stories were exactly the same in both media, were well-written and edited. Typographic cues that give the reader priorities when engaging with the texts were transferred from the print to the online editions. HTML texts to this group are an impediment to the reading process, and the amount of texts require too much time to read. A larger study with a more diverse readership reading more general news is required to verify the findings. This is being planned. As one from the study group stated "I grew up with print but younger people do not have the benefits of print". Practical implications: – Typography provides a language with visual form and through that form, conveys the meaning of a text. The print reader decodes what she reads on the printed page, allowing her to quickly absorb and parse large amount of text, discarding redundant content. The question now becomes which print-reading operations are being transferred to the process of extracting relevant facts. Five centuries of continuous improvement of print communications have yet to be successfully transferred to the Internet. The visual aspects of print, the color advertisement, the photograph and elements that aided the print reader's navigation are an intrusion on the Web. A new form of navigation, one that is more elegant and intuitive than the present, is required. Social implications: – The social implications of reading are a fundamental characteristic of any society. The codex provided the model for the book, the newspaper and the magazine. These became and still are trusted sources of information. When the study group gets a Twitter or Facebook prompt on a breaking news story, they check a trusted broadcasting source for confirmation of its accuracy. If the findings of this study are confirmed in subsequent research studies on the process of reading online, it will have profound implications for the industry. Publishing to be successful requires the reader to engage with and respond to a message. There is strong evidence that this is not the case with what the advertising industry would consider an important core audience, the Internet "reader". Originality/value: – As a newspaper and magazine designer and teacher, the author been increasingly concerned with the transfer of information from the printed page to the computer screen. Many studies have been conducted on aspects of reading and designing for online reading. They are very often inaccurate and as such inconclusive. Reading is complex and measuring it difficult. The author conducted this study as both a designer and from an academic perspective. It is hoped that it encourages a robust debate.